Produção de lipases e biossurfactantes por bactérias isoladas de um solo contaminado com óleo vegetal. - Carvalho, Laís Campos Teixeira de (2012)
The lipases and biosurfactants produced by microorganisms are involved in the metabolism of oil substrates and they receive great biotechnological interest. In this work the production of lipases and biosurfactants by bacteria isolated from soil used for discard of the residual vegetable oil was analyzed. The 66 strains tested demonstrated lipolytic activity on the tributirine agar. In the rhodamine B agar medium with olive oil or soy oil, the number of lipolytic strains varied from 31,8% to 37,8%, depending on the substrate and medium pH. Lipolytic activity of the 25 positive strains in the rhodamine B agar with olive oil, analyzed by titrimetric method varied from 0.62 U/mL/min to 12.4 U/mL/min. The most active strain in the lipases production, identified as the species belonging to the Burkholderia cepacia complex by 16S rRNA gene sequencing analysis, was submitted to the Surface Respond Methodology analysis to determine the optimal conditions of pH and temperature. The Burkholderia sp. O19 strain showed high lipolytic activity in wide range of pH and temperature, and the highest activity was predicted for pH and temperature above 8.5 and 65oC. All of the bacterial strains showed to produce biosurfactants in at least one of the three analyzed methods. The test of dispersion of the diesel oil allowed the biosurfactants detection in all of the strains, while the oil emulsification and hemolytic activity were observed in 73% and 59% of the strains, respectively. The soil used for the disposal of vegetable oil proved conducive to prospecting of lipolytic microorganisms and producers biosurfactants.